2012
DOI: 10.1111/j.1365-2222.2012.03993.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mite allergic patients in a diverse territory by improved diagnostic tools

Abstract: An improved diagnosis algorithm has been established. Group 2 allergens seem to have a leading role in mite allergy, but as group 1 sensitization could be species-specific in some patients and its prevalence is higher in children, an adequate balance on major mite species and major allergens must be consider in the design of mite allergy vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
(43 reference statements)
9
51
5
Order By: Relevance
“…Moreover, the importance of dual sensitization was confirmed in an area of high HDM exposure and relevance in respiratory allergy (ie, Galicia in northeastern Spain) [6][7][8]. Consequently, the correlation between sIgE to Der p 1 and sIgE to Der p 2 was stronger than that observed in more general populations in Spain [15] [6][7][8]. It therefore seems reasonable to assume that different conclusions could be reached in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the importance of dual sensitization was confirmed in an area of high HDM exposure and relevance in respiratory allergy (ie, Galicia in northeastern Spain) [6][7][8]. Consequently, the correlation between sIgE to Der p 1 and sIgE to Der p 2 was stronger than that observed in more general populations in Spain [15] [6][7][8]. It therefore seems reasonable to assume that different conclusions could be reached in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…In a Spanish population of mite allergic patients (both children and adults), specific IgE to eight allergens, skin prick testing (SPT) to whole mite extracts, level of mite allergen exposure, and specific IgG4 were determined [39]. The results showed that sensitization to Der p 1 was more frequent in children, whereas Lep d 2 sensitization was more frequent in adults.…”
Section: Main Immunological Changes Induced By Aitmentioning
confidence: 97%
“…In China, data on the role of Der p 1 and Der p 2 are still scarce, with only 2 studies confirming the importance of both allergens, 1 using crossed immunoelectrophoresis [8] and the other an allergen microarray [9] . Serologically, the relative importance of Der p 1 and Der p 2 has been reported to be very similar [10][11][12][13] in the European and Australian studies but, based on cross-sectional studies of different age groups, the importance of Der p 2 relative to Der p 1 seems to increase slightly with age [14] . For China, such data have not yet been reported.…”
mentioning
confidence: 99%